2008
DOI: 10.1103/physrevlett.101.254503
|View full text |Cite
|
Sign up to set email alerts
|

Shock Front Width and Structure in Supersonic Granular Flows

Abstract: The full structure of a shock front around a blunt body in a quasi-two-dimensional granular flow is studied. Two features, a large density gradient and a very small thickness of the front, characterize this shock and make it different from shocks in molecular gases. Both of these features can be understood using a modified version of the granular kinetic theory. Our model separates the particles into two subpopulations: fast particles having experienced no collisions and randomly moving particles. This separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 24 publications
6
40
0
Order By: Relevance
“…While the shock front may in principle be described in a kinetic theoretical approach 45 , it is singular from the point of view of hydrodynamics: its width ǫ is microscopic, of order a few mean free paths in the gas at rest, and the velocity distribution of particles in the front is multimodal as some are excited and other immobile (and yet other fall in-between).…”
Section: Shock Front and Rankine-hugoniot Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the shock front may in principle be described in a kinetic theoretical approach 45 , it is singular from the point of view of hydrodynamics: its width ǫ is microscopic, of order a few mean free paths in the gas at rest, and the velocity distribution of particles in the front is multimodal as some are excited and other immobile (and yet other fall in-between).…”
Section: Shock Front and Rankine-hugoniot Conditionsmentioning
confidence: 99%
“…Therefore, the aforementioned experiments 17,18 belong to a corpus of mostly empirical and numerical studies on shocks in other types of granular flow: nonlinear acoustic waves and solitons 37,38 with analytical unidimensional models [39][40][41] , and shocks caused by an obstacle in the flow [42][43][44][45] .…”
Section: Granular Shocksmentioning
confidence: 99%
“…The front is advancing at a velocity U (t). In the high Mach number limit (which is the case here as M ∼ 10, since the velocity of sound is near 10 cm/s while typical velocities of the front are of order 100 cm/s) [5,8], and in the simplest possible form, we can write the shock conditions as follows:…”
Section: Analysis Of the Instabilitymentioning
confidence: 99%
“…As mentioned above, recent work has shown that dilute granular flows may be used to understand the structure of shock waves and the dynamics of blasts [4][5][6][7][8][9]20]. Besides the advantage that blast propagation can be captured with relative ease in granular flows, this system has the additional feature of possessing inelastic collisions so the role of dissipation can be gauged precisely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation